2010
DOI: 10.3945/jn.109.113159
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Multi-Dimensional Approach for Studying the Links between Food Access and Consumption

Abstract: Research on neighborhood food access has focused on documenting disparities in the food environment and on assessing the links between the environment and consumption. Relatively few studies have combined in-store food availability measures with geographic mapping of stores. We review research that has used these multi-dimensional measures of access to explore the links between the neighborhood food environment and consumption or weight status. Early research in California found correlations between red meat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 43 publications
5
102
0
1
Order By: Relevance
“…Our results regarding multifaceted barriers leading people to unhealthy eating echo the findings of several previous studies which portray the broad range of factors and processes underlying the daily food choices of people (Devine et al, 1999;Furst, Connors, Bisogni, Sobal, & Falk, 1996;Krebs-Smith & Kantor, 2001;Newcombe et al, 2012;Rose, Bodor, Hutchinson, & Swalm, 2010;Sobal & Bisogni, 2009). The food choice model suggests "that the personal food system" be cognitive processes that guide individuals' eating behaviors in particular settings (Furst et al, 1996;Sobal & Bisogni, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Our results regarding multifaceted barriers leading people to unhealthy eating echo the findings of several previous studies which portray the broad range of factors and processes underlying the daily food choices of people (Devine et al, 1999;Furst, Connors, Bisogni, Sobal, & Falk, 1996;Krebs-Smith & Kantor, 2001;Newcombe et al, 2012;Rose, Bodor, Hutchinson, & Swalm, 2010;Sobal & Bisogni, 2009). The food choice model suggests "that the personal food system" be cognitive processes that guide individuals' eating behaviors in particular settings (Furst et al, 1996;Sobal & Bisogni, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Based on the economic conceptual framework proposed by Rose et al (2010) that accounts for the idea that food environment influences food purchases, I modified it to include food intake and BMI, the final health and diet outcomes influenced by the food environment. In this framework I included other variables affecting dietary intake and BMI as well, such as physical activity.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Tastes and preferences are influenced mainly by social acceptability of the characteristics of the food in the stores, the promotional effect of products within stores, and the socio-demographic characteristics of individuals. Rose et al (2010) emphasized the use of food cost instead of food price because the first accounts for the real opportunity cost of food incurred by people, which includes food price and the resources spent in travelling the distance to the outlet and buying food that people implicitly include in the maximization of their utility. Distance travelled depends on vehicle ownership or transportation means, and on some dimensions of the food environment indicated by the number and type of food outlets (or their in-store characteristics) and their location relative to places such as home, school, or work.…”
mentioning
confidence: 99%
“…In a related study by [15], it was found that environmental influences (including location and accessibility to shops) determine food choice and consumption. Other factors were indicated to be social acceptability, promotional or advertising effects, cost and availability of foods.…”
Section: Food Choice Determinantsmentioning
confidence: 99%
“…A multitude of studies have dwelt on food choice determinants, for instance, [16], which had a broad scope and employed qualitative methods; [1], [5] and [15], which only reviewed existing literature. However, it appears that there is little empirical research investigating the structure and relativity of these determinants.…”
Section: Introductionmentioning
confidence: 99%